Nitrogen Deposition Enhances Photosynthesis in Moso Bamboo but Increases Susceptibility to Other Stress Factors - Zhang, Rui; Wu, Jiasheng; Li, Quan; Hänninen, Heikki; Peng, Chunju; Yao, Hang; Song, Xinzhang; Ying, Yeqing (Frontiers in Plant Science, 2017)
Atmospheric nitrogen (N) deposition can increase the susceptibility of vascular plants to other stresses, but the physiological basis of such a response remains poorly understood. This study was designed to clarify the physiological mechanisms and evaluate bioindicators of N deposition impact on vascular plants. Here, we evaluate multiple physiological responses to approximately 4 years of simulated additional N deposition (30 to 90 kg N ha-1 yr-1) on three age-classes (1a, 3a and 5a) of Moso bamboo. A saturating response to the additional N deposition was found both in foliar N concentration and in Pn. However, three- and five-year-old bamboo seemed less tolerant to extremely high N deposition than one-year-old bamboo since they were N saturated at a lower N addition. Furthermore, C/N/P stoichiometric ratios were very sensitive to N deposition in all three-age classes of bamboo, but the responses to N deposition in the various age-classes were diverse. We also found that the highest additional N deposition suppressed stomatal conductance and transpiration rate, suggesting an induced water stress. The stress induced by the high N load was also seen in photochemistry, where it reduced potential and actual photosynthetic use of light energy, diminished photo-protection capacity, and increased risk of the photo-damage. High additional N deposition contributed to a decrease in the foliar soluble protein contents and to an increase in the peroxidase activity (POD). Our study suggested, for the first time, that although the photosynthetic rate was increased by the increased N deposition in Moso bamboo, long-term high N load causes negative effects along with damage to photosystem II. Photochemical parameters are more sensitive than photosynthetic rate, or foliar N concentration, in Moso bamboo under N deposition. Also, plant age should be taken into account when assessing plants’ susceptibility to changes in global change drivers such as N deposition. These findings facilitate the revealing of the risks potentially caused to vascular plants by increased N deposition before any visible symptoms of injury are seen.